General Theoretical, Methodological, and Philosophical Foundations for the Development of a Medical Worldview (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
Our article analyzes the work aimed at ensuring that the modern system of higher medical education, which has arisen as a result of modernization, prepares doctors for a qualitatively new scientific, ideological, and professional level. In this regard, it is necessary to radically resolve the issues of the content, structure, and technology of training highly qualified doctors in higher medical education. Attention should be paid to the training of doctors with well-founded specialist knowledge and a comprehensive worldview who can successfully solve new tasks in the health sector defined in the project